Evaluasi Usability Pada Website Malangmenyapa.malangkota.go.id Dinas Kebudayaan dan Pariwisata Kota Malang Menggunakan Metode Usability Testing - Muhammad Faishal Erwin; Niken Hendrakusma Wardani; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The purpose of this study was to determine the usability problems of malangmenyapa.malangkota.go.id in the Culture and Tourism Office of Malang City using the usability testing method and provide recommendations for improvements in the form of Prototype. The method used in this study is the usability testing and interview methods to conduct problem excavation on the Malang Menyapa website and to measure the usability level of malangmenyapa.malangkota.go.id using task scenario and questionnaire. Task scenario testing and interviews were conducted with 5 participants and filling out questionnaires was carried out by 20 respondents consisting of new users and old users from the website malangmenyapa.malangkota.go.id. The results of this study found 4 problems, namely the appearance that is still messy, there is no fast search feature, some features of social media links are not active, and the event list display is too much to load on one page. The results of the initial usability test level include the user convenience level of 74 percent, the user speed level of 0.04 goals / sec, the user error rate of 0.084, and the user satisfaction level of 63.5. After repairs on the appearance of the website, the results of usability levels at the user's convenience level increased to 98 percent, the user speed level increased to 0.10 goals / sec, the user error rate decreased to 0.010 and the user satisfaction level was 81.1